The Maui millionaires for business : - Finkel, David (John Wiley, 2008)
This book is like an accelerated graduate program on how to build your business and grow your personal fortune. You'll learn how to: Build a business that works for you—not the other way around; Triple your business's cash flow and increase your personal net worth tenfold; Grow your wealth independent of your business for long-term financial security; Find a deeper meaning—beyond just the money—to sustain you and your business in the long run... You can have the freedom and financial success that you desire when you learn to build your business and your wealth the Maui Millionaire way!